2021
DOI: 10.1093/jac/dkab199
|View full text |Cite
|
Sign up to set email alerts
|

Pyocin efficacy in a murine model of Pseudomonas aeruginosa sepsis

Abstract: Background Bloodstream infections with antibiotic-resistant Pseudomonas aeruginosa are common and increasingly difficult to treat. Pyocins are naturally occurring protein antibiotics produced by P. aeruginosa that have potential for human use. Objectives To determine if pyocin treatment is effective in a murine model of sepsis with P. aeruginosa. Methods Reco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…A recent study showed that colicins can be used to disrupt biofilm integrity [223]. Moreover, when injected into the bloodstream of mice, pyocin S5 was observed to retain its functionality and to improve mouse survival to Pseudomonas infections [224]. Another study demonstrated that microcapsule delivery of the active form of colicin Ia reduced E. coli colonisation in murine models [225].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that colicins can be used to disrupt biofilm integrity [223]. Moreover, when injected into the bloodstream of mice, pyocin S5 was observed to retain its functionality and to improve mouse survival to Pseudomonas infections [224]. Another study demonstrated that microcapsule delivery of the active form of colicin Ia reduced E. coli colonisation in murine models [225].…”
Section: Discussionmentioning
confidence: 99%
“…When the 32 clinical isolates were tested against the 32 isolated pyocins, none were able to lyse the source strain or those strains with the same serotype or ST. As previously described, variability in the susceptibility to the pyocins was observed between those isolates that shared ST and/or serotype and the same type of pyocin, probably due to the frequently observed mutations in the LPS genes in CF, affecting recognition by the RBP 7,26,27 . Pyocins have been considered potential alternatives to antibiotics, and several studies have demonstrated antimicrobial activity of pyocins alone or in combination with other antimicrobials and those sharing the LPS as target 9,19,20,28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…The R-type pyocins were used for the rst time in 1969 to rescue chick embryos infected with P. aeruginosa 17 . In addition, several assays in murine models con rmed the e cacy of R-type pyocins in the treatment of infections with P. aeruginosa 9,18,19 . Due to the narrow spectrum of the PTLBs, some studies focused on generating recombinant R-type pyocins to retarget them by substituting the tail ber protein with a phage protein in order to increase the host range in several species such as P. aeruginosa, Clostridioides di cile and Listeria monocytogenes 8,20−23 .…”
Section: Introductionmentioning
confidence: 99%
“…In the competition for the ecological niche, bacteria develop multiple mechanisms to ensure their survival and predominance. PA produces siderophores, such as pyoverdine, pyochelin and pyocianin (i.e., PyoS5), to bind iron and to transport it from the extracellular region into the bacterium through the outer membrane receptor FptA, a TonB-dependent transporter (70)(71)(72)(73)(74)(75)(76).…”
Section: Virulome Modulated Proteinsmentioning
confidence: 99%